Pengaruh Penggunaan Media “Smart Lung” Berbasis Model Discovery Learning Terhadap Hasil Belajar IPAS Materi Sistem Pernapasan Manusia Kelas VB SDK Maria Ferrari: (The Effect of Using “Smart Lung” Media Based on the Discovery Learning Model Regarding the IPAS Learning Result for Human Respiratory System Material for Class VB SDK Maria Ferrari) - Nona Erwin, Elisabeth Viani; Lawotan, Yohanes Ehe; Maria, Sonya Kristiani (BIODIK, 2025)
This study aims to determine the effect of using the "Smart Lung" media on the learning outcomes of students in the VB SDK Maria Ferrari class on the human respiratory system in science studies. This study was a quantitative pre-experimental study using a one-group pretest-posttest design. It was conducted on one group without a control or comparison group. Data collection techniques used were learning outcome tests and documentation. The sampling technique used in this study was a saturated sampling technique with 30 students in the VB SDK Maria Ferrari class. Data analysis techniques used in this study included normality testing and hypothesis testing. The results showed that the use of the "Smart Lung" media had an effect on the learning outcomes of students in the VB SDK Maria Ferrari class on the human respiratory system in science studies. The average pretest score was 67.67 and the average posttest score increased to 81.33. This indicates an improvement in student learning outcomes after using the "Smart Lung" media. Based on the t-test output table, a significance value of 0.001 < 0.05 was obtained, which means the null hypothesis (H0) stating that "there is no difference in learning outcomes before and after treatment" is rejected, and the alternative hypothesis (Ha) stating "there is a difference in learning outcomes before and after treatment" is accepted. Therefore, it is reasonable to state that the use of "Smart Lung" media has an effect on the learning outcomes of class VB students at SDK Maria Ferrari. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media “Smart Lung “  terhadap hasil belajar IPAS materi sistem pernapasan manusia kelas VB SDK Maria Ferrari. Jenis penelitian ini adalah kuantitatif pre-eksperimental dengan menggunakan rancangan one-group pretest-posttes design. Dilakukan terhadap satu kelompok tanpa adanya kelompok kontrol atau pembanding. Teknik pengumpulan data yang digunakan adalah soal tes hasil belajar dan dokumentasi. Teknik pengambilan sampel dalam penelitian ini adalah teknik sampling jenuh sebanyak 30 orang siswa kelas VB SDK Maria Ferrari. Teknik analisis data yang digunakan dalam penelitian ini adalah uji normalitas dan uji hipotesis. Dari masing-masing hasil yang diperoleh menunjukan bahwa adanya pengaruh penggunaan media “Smart Lung” terhadap hasil belajar IPAS materi sistem pernapasan manusia kelas VB SDK Maria Ferrari dengan diperoleh nilai rata-rata pretest siswa adalah 67,67 dan nilai rata-rata pada posttest meningkat menjasdi 81,33. Ini berarti terjadi peningkatan hasil belajar siswa setelah menggunakan media “Smart Lung”. Berdasarkan tabel output hasil uji t, diperoleh nilai signifikansi 0,001 < 0,05, yang artinya hipotesis nol (H0) yang menyatakan bahwa “tidak terdapat perbedaan hasil belajar sebelum dan sesudah perlakuan” ditoklak, dan hipotesis alternatif (Ha) yang menyatakan “terdapat perbedaan hasil belajar sebelum dan sesudah perlaukuan” diterima. Dengan begitu layak dinyatakan bahwa terdapat pengaruh penggunaan media “Smart Lung” terhadap hasil belajar siswa kelas VB SDK Maria Ferrari.